The Paradox of Parks in Low-Income Areas: Park Use and Perceived Threats. (January 2016) - Cohen, Deborah A.; Han, Bing; Derose, Kathryn P.; Williamson, Stephanie; Marsh, Terry; Raaen, Laura; McKenzie, Thomas L.
Concerns about safety and perceived threats have been considered responsible for lower use of parks in high-poverty neighborhoods. To quantify the role of perceived threats on park use, we systematically observed 48 parks and surveyed park users and household residents in low-income neighborhoods in the City of Los Angeles. Across all parks, the majority of both park users and local residents perceived parks as safe or very safe. We noted apparently homeless individuals during nearly half of all observations, but very few instances of fighting, intimidating groups, smoking, and intoxication. The presence of homeless individuals was associated with higher numbers of park users while the presence of intoxicated persons was associated with lower numbers. Overall, the strongest predictors of increased park use were the presence of organized and supervised activities. Therefore, to increase park use, focusing resources on programming may be more fruitful than targeting perceived threats.